Sea of plastic: representations of the sea and pro-environmental attitudes and behaviors regarding marine plastic pollution in Peru and Chile - Saavedra, Fernanda; Mego, Marisol; Ticona, Sofia; Thiel, Martin; Baeza, Jostein; Espinosa, Agustín (Frontiers in Psychology, 2024)
Marine plastic pollution remains one of the greatest problems worldwide. Hence, this study explores the attitudes and pro-environmental behaviors of Peruvian and Chilean citizens regarding marine pollution, with an emphasis on plastic pollution. For this, forty-four semi-structured interviews were conducted with Peruvian (n=24) and Chilean (n=20) citizens, of which, through thematic analysis, semantic patterns were identified. Results show that the participants' representation of the sea is positive and related to the connection they report having with this environment. Additionally, it was found that the sea fulfills recreational and economic purposes, reflecting an anthropocentric perspective, since it is associated with leisure and resource extraction, respectively. Both purposes are related to the causes of plastic pollution, although with differentiated effects. Anthropocentrism is also reflected in the direction that environmental concern takes towards the impact of this type of pollution predominately on individuals and society. Regarding pro-environmental behaviors, most of the initiatives proposed by the participants in response to marine plastic pollution correspond to individual actions, which could be due to the fact that they perceive a low commitment level from authorities to address the problem. In particular, the Chilean participants attributed a greater role to their authorities in dealing with plastic pollution, which would indicate a more institutional perspective of the problem. Thus, it is proposed that to address marine plastic pollution it is necessary to articulate individual PAGE \* Arabic \* MERGEFORMAT actions with public policies carried out by social stakeholders such as governments, companies and non-governmental organizations, in order to build a more efficient culture of marine protection.